Mehanske lastnosti spajkanih spojev - Zorc, Borut (Kovine zlitine tehnologije, 1997)
A study of mechanical properties and analysis of microstructure of brazed joints with carbon structural steel (brazing filler material: L-Ag40Cd), stainless steel 18-8 (brazing filler metals: L-Ag40Cd and L-Ni7), copper and brass (brazing filler metal: L-CuP7) were made. A comparison of the mechanical properties of the brazed joints and of those of the parent metal subject to thermal cycles during brazing was made.
Keywords: varilstvo; spajkanje; zlitine; mehanske lastnosti; metalografske preiskave; spajke; talila